2003
DOI: 10.1007/s00421-003-0827-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brisk walk on lipoprotein lipase activity and plasma triglyceride concentrations in the fasted and postprandial states

Abstract: The introduction of this article stated that 'low density lipoprotein' are a feature of the atherogenic lipoprotein phenotype. This was a misprint and should have stated that 'small dense low density lipoprotein' are a feature of the atherogenic lipoprotein phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…The most likely explanation for this apparent discrepancy is the fact that participants stopped lipid-lowering medication 2 weeks prior to the study, a period that may have been too short. Both Sit Less and Exercise resulted in lower fasting plasma triacylglycerol levels, which may be the result of increased triacylglycerol clearance due to enhanced lipoprotein lipase activity [31]. These observed lower triacylglycerol levels after physical activity are in line with previous [16,31] but not all [15] studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most likely explanation for this apparent discrepancy is the fact that participants stopped lipid-lowering medication 2 weeks prior to the study, a period that may have been too short. Both Sit Less and Exercise resulted in lower fasting plasma triacylglycerol levels, which may be the result of increased triacylglycerol clearance due to enhanced lipoprotein lipase activity [31]. These observed lower triacylglycerol levels after physical activity are in line with previous [16,31] but not all [15] studies.…”
Section: Discussionsupporting
confidence: 78%
“…Both Sit Less and Exercise resulted in lower fasting plasma triacylglycerol levels, which may be the result of increased triacylglycerol clearance due to enhanced lipoprotein lipase activity [31]. These observed lower triacylglycerol levels after physical activity are in line with previous [16,31] but not all [15] studies. In the latter study, however, triacylglycerol levels were probably measured too soon after exercise, as lipoprotein lipase activity typically peaks ≥8 h post exercise.…”
Section: Discussionsupporting
confidence: 78%
“…However, since we did not observe interaction effects between groups for maximal oxygen uptake and pre-heparin serum LPL, it is not known whether a higher volume of exercise training would increase pre-heparin serum LPL concentrations. Nevertheless, several studies have shown that the magnitude of change in post-heparin blood LPL activity or skeletal muscle LPL activity is much smaller after performing an acute bout of moderate-intensity/ moderate-volume exercise [24][25][26] . Thus, it is possible that a high volume of exercise may be required to increase the pre-heparin serum LPL concentration, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Two other reports have demonstrated that exercise-induced decreases in postprandial lipaemia do not necessarily coincide with increases in LPL activity. Herd et al [33] found that 90 min of moderate exercise did not increase mean skeletal muscle LPL activity 18 h following exercise despite significantly reducing postprandial lipaemia at this time, and Gill et al [32] similarly reported that 90 min of moderate exercise did not significantly increase fasting or postprandial post-heparin LPL activity on the day following exercise despite significantly reducing fasting and postprandial TG concentrations. In the latter two studies [32,33], the subjects experiencing the largest exercise-induced TG reductions also had the greatest increases in LPL.…”
Section: Evidence For Mechanisms Other Than Increased Tg Clearancementioning
confidence: 98%